ANALISIS SEKTOR PERIKANAN TERHADAP PEMBANGUNAN WILAYAH KABUPATEN LAMONGAN - Titik, Crisanty Sutristyaningtyas; Fatmawati, Nurul Indah (JEB17 : Jurnal Ekonomi dan Bisnis, 2020)
Lamongan Regency has considerable fisheries sector potential so that the East Java Provincial Government has designated the northern region of Lamongan Regency as a special economic zone focusing on the maritime industry sector with a land supply of around 200 Ha. However, the value of Lamongan Regency's fisheries production is lagging far behind that of other sectors. For this reason, researchers need to know which comodities are the leading especially in the marine capture fisheries subsector. In addition, researchers must also identify whether the fisheries sector has competitive competitiveness, has good growth performance.Analysis of the data used in this research is quantitative descriptive with the method used to answer the predetermined problems is Localization Index Analysis (LI) and Specialization Index Analysis (SI) to find out whether there is a superior focus and also typical activities in the fisheries sector. The results show that in Lamongan District the fisheries sector has not been a prime focus and has not been a unique activity. Location Quotient Analysis (LQ) to identify the economic base (base sector) in the marine capture fisheries subsector. Produce that the type of kakap merah, squid, and swanggi become the base sector for 5 years. Data Envelopment Analysis (DEA) to measure the efficiency of marine fisheries in Lamongan Regency compared to the Regency / City in East Java as its DMU, the results are were found that the level of efficiency of marine capture fisheries in Lamongan Regency occurred in 2015 and 2016. Keywords: Location Quotient (LQ), Localization Index (LI), Specialization Index Analysis (SI), Data Envelopment Analysis (DEA), fisheries sector.